2020
DOI: 10.1111/jbi.13802
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal diversity predicted to substantially decline due to climate changes in North American Pinaceae forests

Abstract: Aim Ectomycorrhizal fungi (ECMF) are partners in a globally distributed tree symbiosis implicated in most major ecosystem functions. However, resilience of ECMF to future climates is uncertain. We forecast these changes over the extent of North American Pinaceae forests. Location About 68 sites from North American Pinaceae forests ranging from Florida to Ontario in the east and southern California to Alaska in the west. Taxon Ectomycorrhizal fungi (Asco‐ and Basidiomycetes). Methods We characterized ECMF commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 70 publications
(108 reference statements)
3
40
0
Order By: Relevance
“…Specifically, we found the psychrophilic basidiomycete yeast Guehomyces pulullans [57] and a few cold adapted Ascomycete yeasts identified in Vu, Groenewald, Szöke, Cardinali, Eberhardt, Stielow, de Vries, Verkleij, Crous, Boekhout and Robert [58], including Naganishia adeliensis and Udenomyces megalosporus (= U. pyricola in Vu et al 2016). We also found the psychrophiles Elasticomyces elasticus and Mrakia sp., which had been detected in previous soil surveys in both West Yellowstone and Hyalite near Cooke City, Montana [59]. Additionally, our Tausonia pamirica OTU matched 100% to the sequence of the type specimen (Genbank # NR_154490), a known psychrotolerant yeast from Antarctica [60].…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, we found the psychrophilic basidiomycete yeast Guehomyces pulullans [57] and a few cold adapted Ascomycete yeasts identified in Vu, Groenewald, Szöke, Cardinali, Eberhardt, Stielow, de Vries, Verkleij, Crous, Boekhout and Robert [58], including Naganishia adeliensis and Udenomyces megalosporus (= U. pyricola in Vu et al 2016). We also found the psychrophiles Elasticomyces elasticus and Mrakia sp., which had been detected in previous soil surveys in both West Yellowstone and Hyalite near Cooke City, Montana [59]. Additionally, our Tausonia pamirica OTU matched 100% to the sequence of the type specimen (Genbank # NR_154490), a known psychrotolerant yeast from Antarctica [60].…”
Section: Discussionsupporting
confidence: 69%
“…Our results emphasized that both abundant bacterial and fungal sub-communities had higher niche breadths, which re ected their adaptations to broader ranges of environmental gradients. Environmental threshold analysis based on TITAN has been reported in some biodiversity-related studies [17,30,55]. For instance, ectomycorrhizal fungal diversity in North American…”
Section: Discussionmentioning
confidence: 99%
“…Pinaceae forests determines large effects on ectomycorrhizal fungi-associated biogeochemical cycles [55]. The results of environmental breadths of microbes based on environmental threshold analysis are attractive, but are also controversially discussed regarding implications to the real eld situation.…”
Section: Discussionmentioning
confidence: 99%
“…While relative abundance of plant fungal pathogens will probably increase in most regions of the world in the near future because of the increasing global temperature (Delgado-Baquerizo et al, 2020a), Steidinger et al (2020), based on model predictions, forecast a substantial decline in ectomycorrhizal fungal diversity in North American coniferous forests. Even mitigation of greenhouse gas emissions during the 21 st century would probably not stop the decline in ectomycorrhizal fungal diversity (Steidinger et al, 2020). Similarly, a recent meta-study focused on soil mycobiome data across the world, identified that in general ectomycorrhizal fungi tend to have narrower climatic niches compared to free living saprotrophs or fungal plant pathogens (V etrovsk y et al, 2019).…”
mentioning
confidence: 99%
“…While relative abundance of plant fungal pathogens will probably increase in most regions of the world in the near future because of the increasing global temperature (Delgado‐Baquerizo et al ., 2020a), Steidinger et al . (2020), based on model predictions, forecast a substantial decline in ectomycorrhizal fungal diversity in North American coniferous forests. Even mitigation of greenhouse gas emissions during the 21 st century would probably not stop the decline in ectomycorrhizal fungal diversity (Steidinger et al ., 2020).…”
mentioning
confidence: 99%